Interactions Between Experience, Genotype and Sex in the Development of Individual Coping Strategies - Ventura, Rossella; Cabib, Simona; Babicola, Lucy; Andolina, Diego; Di Segni, Matteo; Orsini, Cristina (Frontiers in Behavioral Neuroscience, 2021)
Coping strategies, the first line of defense against adversities, develop through experience. There is consistent evidence that both genotype and gender contribute to the development of dysfunctional coping, leading to maladaptive outcome of adverse experiences or to adaptive coping that fosters rapid recovery even from severe stress. However, how these factors interact to influence the development of individual coping strategies is just starting to be investigated. In the following review we will consider evidence that experience, gender and genotype influence the brain circuits and neurobiological processes involved in coping with adversities and discuss recent results pointing to the specific effects of the interaction between early experiences, genotype and stress in the development of functional and dysfunctional coping styles.